Faktor-Faktor yang Berpengaruh pada Niat Memanfaatkan Insentif Pajak pada Masa Pandemi COVID-19 - Noviari, Naniek; Damayanthi, I Gst Ayu Eka (E-Jurnal Akuntansi, 2021)
This study aims to verify the factors that influence the intention to use tax incentives during the COVID-19 pandemic. The research population is all MSME taxpayers registered in Bali using the accidental sampling method. Data was collected from 100 respondents through a questionnaire using google forms. The analytical tool used in this research is multiple linear regression analysis. The results showed that the perceived tax knowledge, tax risk, internal influence, external influence, self-efficacy, and controlability variables had a positive effect on the intention to use tax facilities. The results of this study can be used as evaluation material in preparing and implementing fiscal policies, especially regarding tax facilities in handling the COVID-19 pandemic. Keywords: Perception Of Tax Knowledge; Tax Risk; Internal Influence; External Influences; Self-Efficacy; Controlability; Intention To Use Tax Facilities.